Nickel-based alloy, method for preparing nickel-based alloy casting

By introducing nano CeO2 powder into nickel-based alloys and performing mechanical ball milling and heat treatment, the problem of low fatigue strength and easy cracking of nickel-based high-temperature alloys in investment precision casting is solved, which significantly improves its strength and plasticity and broadens the process window, improve yield and performance.

CN118241079BActive Publication Date: 2025-01-07ZHEJIANG YOUPENG NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410401141.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-01-07
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

During the investment precision casting process of nickel-based high-temperature alloys, there are problems of low fatigue strength and easy cracking of materials, mainly due to insufficient mechanical properties caused by the low strength, segregation, low melting point eutectics and coarse dendrites of the master alloy.

Method used

A nickel-based alloy preparation method is adopted, including removing the oxide layer on the surface of the alloy raw material, mechanical ball milling with CeO2 nano powder after baking, forming a nano-oxide-reinforced nickel-based alloy, and refining through vacuum induction smelting and high temperature superheating conditions. Combined with solid solution-aging heat treatment, nano-oxide reinforced nickel-based alloy castings were prepared.

Benefits of technology

It significantly improves the strength and plasticity of nickel-based alloys, delays the formation and expansion of cracks, broadens the process window for precision casting of investments of nickel-based high-temperature alloys, reduces the risk of holes and cracks, and improves the yield and performance of castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118241079B_ABST
    Figure CN118241079B_ABST
Patent Text Reader

Abstract

The present disclosure provides a method for preparing a nickel-based alloy and a nickel-based alloy casting, wherein the nickel-based alloy includes the following components and specific gravity: chromium Cr: 17.0wt%-20.0wt%, titanium Ti: 2.2wt%-2.8wt%, molybdenum Mo: 4.0wt%-5.0wt%, tungsten W: 4.0wt%-5.0wt%, aluminum Al: 1.0wt%-1.5wt%, cerium dioxide CeO2: 0.001wt%-1wt%, and the rest is nickel. The production process of the disclosed product is simple, there are no special requirements for smelting equipment, the cost is low, and it is conducive to industrialization. From the perspective of component design, the risk of holes and cracks in nickel-based high-temperature alloys during additive manufacturing is reduced, and the process window of nickel-based high-temperature alloy investment casting is broadened, which is convenient for industrial promotion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technique for enhancing the strength and toughness of a nickel-based alloy, and in particular to a method for preparing a nickel-based alloy and a nickel-based alloy casting. Background Art

[0002] Under the general trend of "large size, integration, precision and complex structure" of aerospace product parts, with the development and in-depth research of vacuum investment casting technology in the aerospace manufacturing industry, aerospace engines have higher and higher requirements for the metallurgical quality and mechanical properties of nickel-based high-temperature alloy investment castings, and the application range of materials is also increasing. Some technical problems of investment casting in the production of large-scale thin-walled and complex structure nickel-based high-temperature alloy castings are gradually exposed. At present, the main problems of investment casting nickel-based high-temperature alloy castings are: 1) Low fatigue strength of materials: multiple fatigue cracks appear during high-condition test runs; 2) Electron beam welding castings are prone to cracking: when welding with forgings, cracks always appear on one side of the casting. This is mainly caused by the low strength of high-temperature alloy materials, and the serious segregation, low melting point eutectic and coarse dendrites of the master alloy castings are the main reasons for its low mechanical properties. The master alloy itself has poor fluidity, poor melt filling and shrinkage compensation capabilities, developed dendrites, and low casting yield. In order to ensure the yield of alloy components, high casting temperature and mold shell insulation temperature are often used. However, this method has obvious disadvantages: the casting product needs to dissipate more heat for solidification, the solidification time is longer, the grains have sufficient time to grow, and the dendrites are more developed.

[0003] Grain refinement of the master alloy can bring about corresponding improvements. There are more capillary transport channels between equiaxed fine grains, smaller intercrystalline gaps, smaller flow resistance, which is conducive to melt shrinkage compensation and has good fluidity. The grains are finer and the grain boundary density is higher. The irregular atomic distribution at the grain boundary will cause a large amount of dislocation accumulation, making the dislocation slip resistance greater, which is manifested as a significant increase in strength on a macro scale. When equiaxed fine grains are deformed, the deformation coordination ability between grains and grains, and between grains and grain boundaries is stronger, the slip band length is shorter, the probability of local stress concentration in the crystal is reduced, the deformation of grain boundaries and within the crystal is more uniform, and the formation and expansion of cracks are delayed. On a macro scale, it is manifested as a significant increase in plasticity and fatigue strength. In recent years, the role of fine grain organization in polycrystalline high-temperature alloys has attracted great attention, and a large number of experimental explorations have been carried out. Among them, the large plastic deformation method for preparing nanocrystalline high-temperature alloys is difficult; the chemical refinement method has strict composition control and is prone to generate harmful precipitation phases; intermetallic compounds are used as refiners and do not change the alloy phase composition, but are of a single type; nanoparticle dispersion strengthening has a significant impact on the performance of high-temperature alloys. For example, Inconel's MA6000 (and its modified MA6000E) is currently the only successfully developed nickel-based high-temperature alloy containing both γ′ phase and Y2O3 nanoparticles, and is designed for engine moving blades with operating temperatures above 1000°C.

[0004] With the development of aviation, the inlet and outlet temperatures of high-performance aircraft hot-end components are increasing, and the high-temperature alloy material issues of aircraft hot-end components are becoming more and more important. As the main material for manufacturing aircraft hot-end components, nickel-based high-temperature alloys have become a development trend to further increase their operating temperature and improve their comprehensive performance. Summary of the invention

[0005] The present disclosure provides a method for preparing a nickel-based alloy and a nickel-based alloy casting, so as to at least solve the above technical problems existing in the prior art.

[0006] According to a first aspect of the present disclosure, a nickel-based alloy is provided, wherein the nickel-based alloy comprises the following components and specific gravities:

[0007] Chromium Cr: 17.0wt%-20.0wt%, titanium Ti: 2.2wt%-2.8wt%, molybdenum Mo: 4.0wt%-5.0wt%, tungsten W: 4.0wt%-5.0wt%, aluminum Al: 1.0wt%-1.5wt%, cerium dioxide CeO2: 0.001wt%-1wt%, and the rest is nickel.

[0008] In some executable embodiments, the nickel-based alloy further includes at least one of the following components:

[0009] Iron Fe: ≤4.0wt%, Carbon C: ≤0.08wt%, Boron B: ≤0.015wt%, Manganese Mn: ≤0.5wt%, Silicon Si: ≤0.6wt%, Phosphorus P: ≤0.015wt%, Sulfur S: ≤0.01wt%.

[0010] In some executable embodiments, the weight ratio of each component in the nickel-based alloy is:

[0011] Iron Fe: 0.06wt%-4.0wt%, carbon C: 0.01wt%-0.08wt%, boron B: 0.001wt%-0.015wt%, manganese Mn: 0.01wt%-0.5wt%, silicon Si: 0.01wt%-0.6wt%, phosphorus P: 0.001wt%-0.015wt%, sulfur S: 0.001wt%-0.01wt%.

[0012] According to a second aspect of the present disclosure, a method for preparing a nickel-based alloy casting is provided, characterized in that the method comprises:

[0013] S1: Preparation of base alloy: remove the oxide layer on the surface of the alloy raw material, place it in a roasting furnace for baking, remove the cutting fluid and oil stains left by surface machining, and set it aside; the components and specific gravity of the base alloy are as follows:

[0014] Chromium Cr: 17.0wt%-20.0wt%, titanium Ti: 2.2wt%-2.8wt%, molybdenum Mo: 4.0wt%-5.0wt%, tungsten W: 4.0wt%-5.0wt%, aluminum Al: 1.0wt%-1.5wt%, and the rest is nickel;

[0015] S2: Preparation of reinforcing phase nano CeO2: Place CeO2 nano powder in a vacuum drying oven for drying, and after drying, mix nano CeO2 with appropriate amount of carburizer and aluminum powder by mechanical ball milling;

[0016] S3: Prepare a casting test rod mold shell by using silica sol firing method, place the prepared mold shell in a sand bucket, fill the mold shell with 6-8 mesh magnesia sand, and then send the sand bucket and the mold shell into a roasting furnace. The roasting temperature is 940℃-955℃; the roasting time is 3.8h-4.1h;

[0017] S4: placing the mixed powder obtained in step S2 at the bottom of a melting crucible in a vacuum induction melting furnace, placing the alloy raw material obtained in step S1 at the upper part of the melting crucible, melting at 1450-1550°C for 30-60min, and then refining at 1600-1650°C for 10min under high superheat conditions; after cooling to 1550°C, quickly pouring it into the mold shell that has been dried and insulated in step S3, during the solidification process, the solid nano-CeO2 evenly distributed in the melt will act as a nucleating agent to induce nucleation, and obtain a nano-oxide reinforced nickel-based alloy composite ingot;

[0018] S5: Performance heat treatment: The casting obtained in step S4 is placed in a heat treatment furnace for a two-step performance heat treatment of solid solution and aging to obtain a nickel-based alloy casting.

[0019] In some executable embodiments, the matrix alloy further includes at least one of the following components:

[0020] Iron Fe: ≤4.0wt%, Carbon C: ≤0.08wt%, Boron B: ≤0.015wt%, Manganese Mn: ≤0.5wt%, Silicon Si: ≤0.6wt%, Phosphorus P: ≤0.015wt%, Sulfur S: ≤0.01wt%.

[0021] In some executable embodiments, the weight ratio of each component in the matrix alloy is:

[0022] Iron Fe: 0.06wt%-4.0wt%, carbon C: 0.01wt%-0.08wt%, boron B: 0.001wt%-0.015wt%, manganese Mn: 0.01wt%-0.5wt%, silicon Si: 0.01wt%-0.6wt%, phosphorus P: 0.001wt%-0.015wt%, sulfur S: 0.001wt%-0.01wt%.

[0023] In some executable embodiments, the drying temperature in step S2 is 195° C.-210° C., and the drying time is 7.8 h-8.1 h.

[0024] In some executable embodiments, the CeO2 nanoparticles described in step S2 have a particle size of 20nm-50nm, a mass of 0.1%-1% of the total mass of the matrix alloy, and the mass proportion of the recarburizer is 0.03%-0.06% of the total mass.

[0025] In some executable embodiments, the rotation speed of the mechanical ball milling in step S2 is 200 rpm-300 rpm, and the ball milling time is 180 min-240 min.

[0026] In some executable embodiments, the heat treatment process described in step S4 is: solution treatment at 1140°C in an Ar gas atmosphere for 2 hours, air cooling; aging at 840°C in an Ar gas atmosphere for 8 hours, and furnace cooling.

[0027] Compared with the fine grain casting with traditional intermediate alloy as refiner, the technical solution disclosed in the present invention has the advantage that nanoparticles not only play the role of refiner, but also can strengthen the matrix and grain boundary strength, improve the medium and low temperature performance of the material, and at the same time, the strong and stable nano oxide does not react with the matrix, and the phenomenon of the refinement effect being weakened due to the extension of the smelting time will not occur. Compared with the metal-based composite materials prepared by the traditional in-situ self-generation method, the alloy reinforcement phase content and particle size disclosed in the present invention are strictly controllable, the particle size is smaller, and the distribution is more uniform. CeO2 nanoparticles are attached to the surface of the carburizer and aluminum powder by high-energy ball milling, which increases their ability to enter the melt and inhibits the occurrence of agglomeration. The production process of the disclosed product is simple, there is no special requirement for smelting equipment, the cost is low, and it is conducive to industrialization. From the perspective of component design, the risk of holes and cracks in nickel-based high-temperature alloys during additive manufacturing is reduced, and the process window of nickel-based high-temperature alloy investment casting is broadened, which is convenient for industrial promotion.

[0028] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0030] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0031] Figure 1 A schematic diagram of a process flow of a method for preparing a nickel-based alloy casting according to an embodiment of the present disclosure is shown;

[0032] Figure 2 A scanning electron microscope photograph of nano-CeO2 used in the embodiments of the present disclosure is shown;

[0033] Figure 3 The schematic diagram of the CeO2 / Ni ingot prepared in the embodiment of the present disclosure is shown in FIG.

[0034] Figure 4 A schematic diagram of a cross-sectional macrostructure (a) of Comparative Example 1 of the disclosed embodiment and a schematic diagram of a cross-sectional macrostructure (b) of Example 1 are shown;

[0035] Figure 5 A schematic diagram of the room temperature mechanical properties of the CeO2 / Ni ingot prepared in the embodiment of the present disclosure is shown. DETAILED DESCRIPTION

[0036] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0037] Figure 1 The process flow diagram of the method for preparing the nickel-based alloy casting according to the embodiment of the present disclosure is shown as follows: Figure 1 As shown, the method for preparing the nickel-based alloy casting according to the embodiment of the present disclosure includes the following processing steps:

[0038] Step S1: Preparation of base alloy: remove the oxide layer on the surface of the alloy raw material, place it in a roasting furnace for baking, remove the cutting fluid and oil stains left by surface machining, and set it aside.

[0039] In the embodiment of the present disclosure, the components and specific gravity of the matrix alloy are as follows:

[0040] Chromium Cr: 17.0wt%-20.0wt%, titanium Ti: 2.2wt%-2.8wt%, molybdenum Mo: 4.0wt%-5.0wt%, tungsten W: 4.0wt%-5.0wt%, aluminum Al: 1.0wt%-1.5wt%, and the rest is nickel.

[0041] The nickel-based alloy further comprises at least one of the following components: iron Fe: ≤4.0wt%, carbon C: ≤0.08wt%, boron B: ≤0.015wt%, manganese Mn: ≤0.5wt%, silicon Si: ≤0.6wt%, phosphorus P: ≤0.015wt%, and sulfur S: ≤0.01wt%.

[0042] Preferably, the weight ratio of each component in the nickel-based alloy is:

[0043] Iron Fe: 0.06wt%-4.0wt%, carbon C: 0.01wt%-0.08wt%, boron B: 0.001wt%-0.015wt%, manganese Mn: 0.01wt%-0.5wt%, silicon Si: 0.01wt%-0.6wt%, phosphorus P: 0.001wt%-0.015wt%, sulfur S: 0.001wt%-0.01wt%.

[0044] Step S2: Preparation of reinforcing phase nano-CeO2: Place CeO2 nano-powder in a vacuum drying oven for drying. After drying, mix nano-CeO2 with appropriate amount of recarburizer and aluminum powder by mechanical ball milling.

[0045] In the disclosed embodiment, the drying temperature is 195°C-210°C, and the drying time is 7.8h-8.1h. The CeO2 nanoparticles have a particle size of 20nm-50nm, a mass of 0.1%-1% of the total mass of the matrix alloy, and a mass proportion of the carburizer of 0.03%-0.06% of the total mass. The speed of the mechanical ball mill is 200rpm-300rpm, and the ball milling time is 180min-240min.

[0046] Step S3: Prepare a casting test rod mold shell by using silica sol firing method, place the prepared mold shell in a sand bucket, fill the mold shell with 6-8 mesh magnesia sand, and then send the sand bucket and the mold shell into a roasting furnace. The roasting temperature is 940℃-955℃; the roasting time is 3.8h-4.1h.

[0047] Step S4: placing the mixed powder obtained in step S2 at the bottom of a melting crucible in a vacuum induction melting furnace, placing the alloy raw material obtained in step S1 at the upper part of the melting crucible, melting at 1450°C-1550°C for 30min-60min, and then refining at 1600°C-1650°C for 10min under high superheat conditions; after cooling to 1550°C, quickly pouring it into the mold shell that has been dried and insulated in step S3, during the solidification process, the solid nano-CeO2 evenly distributed in the melt will act as a nucleating agent to induce nucleation, thereby obtaining a nano-oxide reinforced nickel-based alloy composite ingot.

[0048] Step S5: Performance heat treatment: The casting obtained in step S4 is placed in a heat treatment furnace for a two-step performance heat treatment of solid solution and aging to obtain a nickel-based alloy casting.

[0049] The process of the two-step solution-aging heat treatment is: solution treatment at 1140°C in an Ar atmosphere for 2 hours, air cooling; aging at 840°C in an Ar atmosphere for 8 hours, and furnace cooling.

[0050] The essence of the technical solution of the embodiment of the present disclosure is further explained below through specific embodiments.

[0051] Embodiment 1:

[0052] Step 1, remove the oxide layer on the surface of the alloy raw materials, the alloy raw materials are: 34Kg of chromium, 5Kg of titanium, 8Kg of molybdenum, 8Kg of tungsten, 8Kg of iron, and 134Kg of nickel, and place them in a roasting furnace for baking at a temperature of 200°C for 2 hours to remove the cutting fluid and oil stains left by surface machining;

[0053] Step 2: Place 1 kg of CeO2 nanopowder with a particle size of 20 nm in a vacuum drying oven at 200°C for 8 hours. After drying, mechanically mill the nano CeO2 with 2 kg of aluminum powder and 80 g of recarburizer at a speed of 200-300 rpm for 180-240 minutes. Figure 2 As shown, a schematic diagram of a scanning electron microscope photograph of nano-CeO2 is shown.

[0054] Step 3: The casting shell of the test rod is obtained by firing silica sol. The prepared shell is placed in a sand bucket, and the surrounding is filled with 6-8 mesh magnesia sand. Then the sand bucket and the shell are sent to a roasting furnace, and the roasting temperature is 950°C; the heat preservation time is 4 hours.

[0055] Step 4, placing the mixed powder obtained in step 2 at the bottom of a melting crucible in a vacuum induction melting furnace, placing the alloy raw material obtained in step 1 at the upper part of the melting crucible, melting at 1450° C. for 60 min, and then refining at 1650° C. for 10 min under high superheat conditions; then cooling to 1550° C. and quickly pouring it into the casting mold that has been dried and insulated in step 3 to obtain a nano-oxide reinforced nickel-based high-temperature alloy composite ingot, such as Figure 3 shown.

[0056] Step 5: Place the casting obtained in step 4 in a heat treatment furnace at 1140°C, solution treatment for 2 hours in Ar gas, air cooling, aging at 840°C in Ar gas for 8 hours, and cooling in the furnace.

[0057] Embodiment 2:

[0058] Step 1, remove the oxide layer on the surface of the alloy raw materials, the alloy raw materials are: 34Kg of chromium, 5Kg of titanium, 8Kg of molybdenum, 8Kg of tungsten, 8Kg of iron, and 134Kg of nickel, and place them in a roasting furnace for baking at a temperature of 200°C for 2 hours to remove the cutting fluid and oil stains left by surface machining;

[0059] Step 2: Place 1 kg CeO2 nanopowder with a particle size of 50 nm in a vacuum drying oven at 200°C for 8 hours. After drying, mechanically mill the nano CeO2 with 2 kg aluminum powder and 80 g of recarburizer at a speed of 200-300 rpm for 180-240 minutes.

[0060] Step 3: The casting shell of the test rod is obtained by firing silica sol. The prepared shell is placed in a sand bucket, and the surrounding is filled with 6-8 mesh magnesia sand. Then the sand bucket and the shell are sent to a roasting furnace, and the roasting temperature is 950°C; the heat preservation time is 4 hours.

[0061] Step 4, placing the mixed powder obtained in step 2 at the bottom of a melting crucible in a vacuum induction melting furnace, placing the alloy raw material obtained in step 1 at the upper part of the melting crucible, melting at 1450°C for 60 minutes, and then refining at 1650°C for 10 minutes under high superheat conditions; then cooling to 1550°C and quickly pouring it into the casting mold that has been dried and insulated in step 3 to obtain a nano-oxide reinforced nickel-based high-temperature alloy composite ingot.

[0062] Step 5: Place the casting obtained in step 4 in a heat treatment furnace at 1140°C, solution treatment for 2 hours in Ar gas, air cooling, aging at 840°C in Ar gas for 8 hours, and cooling in the furnace.

[0063] Comparative Example 1:

[0064] Step 1, remove the oxide layer on the surface of the alloy raw materials, the alloy raw materials are: 34Kg of chromium, 5Kg of titanium, 8Kg of molybdenum, 8Kg of tungsten, 8Kg of iron, 2kg of aluminum powder, and 134Kg of nickel, and place them in a roasting furnace for baking at a temperature of 200°C for 2 hours to remove the cutting fluid and oil stains left by surface machining;

[0065] Step 2: Place 1 kg of CeO2 nanopowder with a particle size of 20 nm in a vacuum drying oven at 200° C. and dry for 8 h for later use.

[0066] Step 3: The casting shell of the test rod is obtained by firing silica sol. The prepared shell is placed in a sand bucket, and the surrounding is filled with 6-8 mesh magnesia sand. Then the sand bucket and the shell are sent to a roasting furnace, and the roasting temperature is 950°C; the heat preservation time is 4 hours.

[0067] Step 4, placing the CeO2 nanopowder obtained in step 2 at the bottom of the melting crucible of a vacuum induction melting furnace, placing the alloy raw material obtained in step 1 at the upper part of the melting crucible, melting at 1450°C for 60 minutes, and then refining at 1650°C for 10 minutes under high superheat conditions; then cooling it to 1550°C and quickly pouring it into the casting mold that has been dried and insulated in step 3 to obtain a nano-oxide reinforced nickel-based high-temperature alloy composite ingot.

[0068] Step 5: Place the casting obtained in step 4 in a heat treatment furnace at 1140°C, solution treatment for 2 hours in Ar gas, air cooling, aging at 840°C in Ar gas for 8 hours, and cooling in the furnace.

[0069] Comparative Example 2:

[0070] Step 1, remove the oxide layer on the surface of the alloy raw materials, the alloy raw materials are: 34Kg of chromium, 5Kg of titanium, 8Kg of molybdenum, 8Kg of tungsten, 8Kg of iron, 2kg of aluminum powder, 80g of carburizer, and 134Kg of nickel, and place them in a roasting furnace for baking at a temperature of 200°C for 2 hours to remove the cutting fluid and oil stains left by surface machining;

[0071] Step 2: The casting shell of the test rod is obtained by firing silica sol. The prepared shell is placed in a sand bucket, and the surrounding is filled with 6-8 mesh magnesia sand. Then the sand bucket and the shell are sent to a roasting furnace, and the roasting temperature is 950°C; the heat preservation time is 4 hours.

[0072] Step 3, placing the alloy raw material obtained in step 1 on the upper part of the melting crucible, melting at 1450°C for 60 minutes, and then refining at 1650°C for 10 minutes; then cooling it to 1550°C and quickly pouring it into the casting mold that has been dried and insulated in step 2 to obtain a nano-oxide reinforced nickel-based high-temperature alloy composite ingot.

[0073] Step 4: Place the casting obtained in step 3 in a heat treatment furnace at 1140°C, solution treatment for 2 hours in Ar gas, air cooling, aging at 840°C in Ar gas for 8 hours, and cooling in the furnace.

[0074] like Figure 4 As shown, Comparative Example 1 ( Figure 4 (a) in the photo) and Example 1 ( Figure 4 (b) The results show that after the introduction of nano-CeO2 powder into the nickel-based high-temperature alloy, the grains are significantly refined, and the room temperature strength, yield strength and elongation are all improved.

[0075] The results of Comparative Example 2 and Example 1 show that when nano-CeO2 powder is directly placed into the master alloy melt, the strengthening phase CeO2 powder undergoes a certain degree of agglomeration and the hard phase is unevenly distributed, resulting in defects in the casting structure, which cannot significantly improve the performance and will also cause defects in the components, posing a safety hazard.

[0076] like Figure 5 As shown, the nickel-based high-temperature alloy of the embodiment of the present invention reduces the risk of holes and cracks in the nickel-based high-temperature alloy during additive manufacturing through component design, broadens the process window of nickel-based high-temperature alloy investment casting, thereby greatly improving the tensile strength, yield strength and elongation of the nickel-based high-temperature alloy, and making the metal stronger and tougher.

[0077] The disclosed embodiments also describe a nickel-based alloy, which is prepared by the method for preparing the nickel-based alloy casting of the aforementioned embodiment.

[0078] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved, and this document does not limit this.

[0079] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0080] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A nickel-based alloy, characterized in that: The nickel-based alloy includes the following components and specific gravity: Chromium Cr: 17.0wt%-20.0wt%, titanium Ti: 2.2wt%-2.8wt%, molybdenum Mo: 4.0wt%-5.0wt%, tungsten W: 4.0wt%-5.0wt%, aluminum Al: 1.0wt%-1.5wt%, cerium dioxide CeO2: 0.001wt%-1wt%, and the rest is nickel; The nickel-based alloy further comprises at least one of the following components: iron Fe: ≤4.0wt%, carbon C: ≤0.08wt%, boron B: ≤0.015wt%, manganese Mn: ≤0.5wt%, silicon Si: ≤0.6wt%, phosphorus P: ≤0.015wt%, sulfur S: ≤0.01wt%; The nickel-based alloy is prepared by the following steps: S1: Preparation of base alloy: remove the oxide layer on the surface of the alloy raw material, place it in a roasting furnace for baking, remove the cutting fluid and oil stains left by surface machining, and set it aside; S2: Preparation of reinforcing phase nano CeO2: Place CeO2 nano powder in a vacuum drying oven for drying, and after drying, mix the nano CeO2 powder with the recarburizer and aluminum powder by mechanical ball milling; S3: Prepare a casting test rod mold shell by using silica sol firing method, place the prepared mold shell in a sand bucket, fill the mold shell with 6-8 mesh magnesia sand, and then send the sand bucket and the mold shell into a roasting furnace. The roasting temperature is 940℃-955℃; the roasting time is 3.8h-4.1h; S4: placing the mixed powder obtained in step S2 at the bottom of a melting crucible in a vacuum induction melting furnace, placing the alloy raw material obtained in step S1 at the upper part of the melting crucible, melting at 1450°C-1550°C for 30min-60min, and then refining at 1600°C-1650°C for 10min under high superheat conditions; after cooling to 1550°C, quickly pouring it into the mold shell that has been dried and insulated in step S3, during the solidification process, the solid nano-CeO2 evenly distributed in the melt will act as a nucleating agent to induce nucleation, and obtain a nano-oxide reinforced nickel-based alloy composite ingot; S5: Performance heat treatment: The casting obtained in step S4 is placed in a heat treatment furnace for a two-step performance heat treatment of solid solution and aging to obtain a nickel-based alloy casting; the process of the two-step performance heat treatment of solid solution and aging in step S5 is: 1140°C, solid solution in Ar gas atmosphere for 2 hours, air cooling; 840°C, aging in Ar gas atmosphere for 8 hours, cooling with the furnace.

2. The nickel-based alloy according to claim 1, characterized in that The weight ratios of the components in the nickel-based alloy are: iron Fe: 0.06wt%-4.0wt%, carbon C: 0.01wt%-0.08wt%, boron B: 0.001wt%-0.015wt%, manganese Mn: 0.01wt%-0.5wt%, silicon Si: 0.01wt%-0.6wt%, phosphorus P: 0.001wt%-0.015wt%, sulfur S: 0.001wt%-0.01wt%.

3. A method for preparing a nickel-based alloy casting, characterized in that: The method comprises: S1: Preparation of base alloy: remove the oxide layer on the surface of the alloy raw material, place it in a roasting furnace for baking, remove the cutting fluid and oil stains left by surface machining, and set it aside; the components and specific gravity of the base alloy are as follows: Chromium Cr: 17.0wt%-20.0wt%, titanium Ti: 2.2wt%-2.8wt%, molybdenum Mo: 4.0wt%-5.0wt%, tungsten W: 4.0wt%-5.0wt%, aluminum Al: 1.0wt%-1.5wt%, and the rest is nickel; the matrix alloy also includes at least one of the following components: iron Fe: ≤4.0wt%, carbon C: ≤0.08wt%, boron B: ≤0.015wt%, manganese Mn: ≤0.5wt%, silicon Si: ≤0.6wt%, phosphorus P: ≤0.015wt%, sulfur S: ≤0.01wt%; S2: Preparation of reinforcing phase nano CeO2: Place CeO2 nano powder in a vacuum drying oven for drying, and after drying, mix the nano CeO2 powder with the recarburizer and aluminum powder by mechanical ball milling; S3: Prepare a casting test rod mold shell by using silica sol firing method, place the prepared mold shell in a sand bucket, fill the mold shell with 6-8 mesh magnesia sand, and then send the sand bucket and the mold shell into a roasting furnace. The roasting temperature is 940℃-955℃; the roasting time is 3.8h-4.1h; S4: placing the mixed powder obtained in step S2 at the bottom of a melting crucible in a vacuum induction melting furnace, placing the alloy raw material obtained in step S1 at the upper part of the melting crucible, melting at 1450°C-1550°C for 30min-60min, and then refining at 1600°C-1650°C for 10min under high superheat conditions; after cooling to 1550°C, quickly pouring it into the mold shell that has been dried and insulated in step S3, during the solidification process, the solid nano-CeO2 evenly distributed in the melt will act as a nucleating agent to induce nucleation, and obtain a nano-oxide reinforced nickel-based alloy composite ingot; S5: Performance heat treatment: The casting obtained in step S4 is placed in a heat treatment furnace for a two-step performance heat treatment of solid solution and aging to obtain a nickel-based alloy casting; the process of the two-step performance heat treatment of solid solution and aging in step S5 is: 1140°C, solid solution in Ar gas atmosphere for 2 hours, air cooling; 840°C, aging in Ar gas atmosphere for 8 hours, cooling with the furnace.

4. The preparation method according to claim 3, characterized in that: The weight ratio of each component in the matrix alloy is: Iron Fe: 0.06wt%-4.0wt%, carbon C: 0.01wt%-0.08wt%, boron B: 0.001wt%-0.015wt%, manganese Mn: 0.01wt%-0.5wt%, silicon Si: 0.01wt%-0.6wt%, phosphorus P: 0.001wt%-0.015wt%, sulfur S: 0.001wt%-0.01wt%.

5. The preparation method according to claim 3, characterized in that: In step S2, the drying temperature is 195° C.-210° C., and the drying time is 7.8 h-8.1 h.

6. The preparation method according to claim 3, characterized in that: The particle size of the CeO2 nanopowder described in step S2 is 20nm-50nm, and the mass is 0.1%-1% of the total mass of the base alloy, and the mass proportion of the recarburizer is 0.03%-0.06% of the total mass of the base alloy.

7. The preparation method according to claim 3, characterized in that: The rotation speed of the mechanical ball milling in step S2 is 200 rpm-300 rpm, and the ball milling time is 180 min-240 min.

Citation Information

Patent Citations

  • Highly corrosion-resistant ni-base alloy and its production

    JP1986119641A

  • Cerium and cerium oxide containing alloys, fuel cell system balance of plant components made therefrom and method of making thereof

    US11001915B1